Murder, she meowed [large type] - Mugavero, Liz (Mugavero, Liz. Pawsitively organic mystery., 2019)
Kristan "Stan" Connor must discover who killed the would-be star of her bachelorette party while trying to keep her upcoming wedding from going off the rails --